Inhibition Mechanism of Shell Gasifier Coal Fly Ash Additive on Inner/Outer Layer Ash Deposition in Biomass Fluidized Bed Gasification - XUE Haotian; QIN Yuhong; WANG Yuefeng; DU Yujia; WEI Yuexing; HE Chong; GUO Shugang; CAI Xingrui (Taiyuan Ligong Daxue xuebao)
[Purposes] The research on the inhibition mechanism of ash deposition on the furnace wall of biomass fluidized bed gasification can provide fundamental data for the design of gasifiers with higher thermal efficiency and stable operation. [Methods] In this study, a self-designed deposition probe is used to collect the inner/outer layer of ash depositions on the furnace wall of corn straw and sargassum horneri, and Shell gasifier coal fly ash (Shell ash) is used as an additive. Analytical methods of IC, ICP-MS, SEM, and XRD are employed to quantitatively analyze the inhibition properties of ash deposition. [Findings] The results indicate that the condensation of alkali metal/alkaline earth metal sulphates and alkali metal chlorides play an important role in the formations of ash in the inner layers of corn straw and sargassum horneri gasification. When Shell ash is added at <15% and <10% to the two materials (mass ratio), the formation of phases such as leucite and orthoclase, which have higher relative melting temperatures, inhibits the adhesion of the ash particles and contributs to the loosening of the outer layer deposition ash structure. The inhibition mechanism suggests that both the base-to-acid ratio (RB/A) and n(SiO2+Al2O3) of the outer layer can effectively reflect the effect of Shell ash on the tendency of the outer layer deposition ash.